Prognostisering av slitdelar - Sandberg, Erik (2009)
The agricultural plantingmachines are used just a few weeks every year. That means that the supply of service and spare parts have to be good to make the timeliness costs low at the agricultural hard working periods. The machines wear down successivly when they are used. The wear is harder on some parts than the others on a machine. Spare parts can be dicided into consumables. Wear parts of a product where the consumer expect to purchade a replacement part after some time and true spare parts which refers to parts of a product that may require to be exchanged after an incident of sort.